1995
DOI: 10.1063/1.114139
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical and high resolution electron microscopy studies of flux pinning at grain boundaries in Bi2Sr2CaCu2Ox crystals

Abstract: We have studied the flux pinning behavior of Bi2Sr2CaCu2Ox multicrystalline samples using a magneto-optical flux observation method. When a magnetic field is applied parallel to the ab plane, we find low flux density regions at the intersections of small angle grain boundaries. The flux density distribution can be explained by considering both flux pinning at the small angle grain boundaries and the intrinsic pinning effect at the BiO layers. High resolution electron microscopy observations show that amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For multicrystalline samples the description in terms of pinning inside the grain boundary is also useful. It was successfully applied to the analysis of critical current in Bi-2223 tapes in [125].…”
Section: Pinning By Point Defects and Nonuniformitiesmentioning
confidence: 99%
“…For multicrystalline samples the description in terms of pinning inside the grain boundary is also useful. It was successfully applied to the analysis of critical current in Bi-2223 tapes in [125].…”
Section: Pinning By Point Defects and Nonuniformitiesmentioning
confidence: 99%
“…It is not clear what these defects are. They may be amorphous patches along small-angle grain boundaries [35], or dislocations, for example. Low-angle tilt boundaries are strong links and they conduct current at elevated fields.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that grain boundaries, growth dislocations, crystal structural non-uniformities, impurity phases, precipitates, oxygen vacancies and other microstructural defects can act as effective pinning centers in Bi-based high temperature superconductors [4][5][6][7][8][9]. The introduction of correlated defects such as columnar defects can resist the thermally activated flux flow at high temperatures successfully.…”
Section: Introductionmentioning
confidence: 98%